The Ghost Story 1840-1920 : a cultural history. - Smith, Andrew, 1964- (Manchester : Manchester University Press, 2010)
The Ghost Story 1840-1920: A Cultural History examines the British ghost story within the political contexts of the long nineteenth century. By relating the ghost story to economic, national, colonial and gendered contexts' it provides a critical re-evaluation of the period. The conjuring of a political discourse of spectrality during the nineteenth century enables a culturally sensitive reconsideration of the work of writers including Dickens, Collins, Charlotte Riddell, Vernon Lee, May Sinclair, Kipling, Le Fanu, Henry James and M.R. James. Additionally, a chapter on the interpretation of sp.
Copyright; Contents; Acknowledgements; Introduction; 1 Seeing the spectre: an economic theory of the ghost story; 2 Dickens's spectres: sight, money, and reading the ghost story; 3 Money and machines: Wilkie Collins's ghosts; 4 Love, money, and history: the female ghost story; 5 Reading ghosts and reading texts: spiritualism; 6 Haunted houses and history: Henry James's Anglo-American ghosts; 7 Colonial ghosts: mimicry, history, and laughter; 8 M.R. James's Gothic revival; Conclusion; Bibliography; Index.
Print version record.
Includes bibliographical references and index.
English.
eBooks on EBSCOhost
Keywords: Ghost stories, English -- History and criticism; English fiction -- 19th century -- History and criticism; English fiction -- 20th century -- History and criticism; Literature and society -- Great Britain -- History -- 19th century; Histoires de fantômes anglaises -- Histoire et critique; Roman anglais -- 19e siècle -- Histoire et critique; Roman anglais -- 20e siècle -- Histoire et critique; Littérature et société -- Grande-Bretagne -- Histoire -- 19e siècle.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; LITERARY CRITICISM -- Gothic & Romance; Literature; English fiction; Ghost stories, English; Literature and society; Great Britain; 1800-1999; British ghost story; Charlotte Riddell; Henry James; May Sinclair; Vernon Lee; long nineteenth century; spectral language; spectrality; spirit messages; textual analysis; Criticism, interpretation, etc; History